Modeli cestnega prometa - Šepec, Luka (Matrika, 2017)
Different models of vehicular traffic are discussed. First, empirical data about vehicular traffic are presented, followed by a presentation of the continuum model, kinetic model and the cellular automata model. Along with the presentation of the models, comparison with the real-life vehicular traffic dynamics is made.
Keywords: celični avtomati; cellular automata model; cestni promet; continuum model; kinetic model; kinetični model; kontinuitetni model; vehicular traffic